Les Comores, le Visa Balladur et l’hécatombe au large de Mayotte : une analyse transdisciplinaire de la question complexe des migrations comoriennes - Tiziano Peccia; Rachele Meda (Confins)
This article is an overview on the migratory crisis which is putting strain on the stability of the Comoros islands, with particularly emphasis to the migratory flow to Mayotte. The « visa Balladur » is required for Comoros' citizens in order to move to Mayotte, a French territory; the introduction of this visa caused the number of illegal immigrant to rise sharply. The analysis of this migratory flow makes it possible studying in a transdisciplinary way several issues related to the current situation of the country, but also the role played by the Comoros archipelago in geostrategical and international dynamics. This study is structured into two main parts: a first part of quantitative data analysis, in order to put in context the socioeconomic situation of the Comoros, and a second one, characterized by primary sources and a qualitative approach based on Comoros citizens' interviews and experiences.